Systematic Review of Technology-Based Media in Enhancing Joyful and Meaningful Mathematics Learning through Ethnomathematics Contexts - Ratu Mauladaniyati; Heri Purnomo; Hilma Alia (Universitas Negeri Surabaya, 2025)
Mathematics is often perceived as abstract and difficult, reducing students’ motivation and engagement. To address these challenges, learning approaches that are joyful and meaningful are increasingly emphasized. Ethnomathematics provides cultural contexts that make mathematics relevant, while technology-based media enhance interactivity and engagement. Yet, research combining these two approaches remains fragmented. This study conducted a systematic review using the PRISMA 2020 protocol, synthesizing 38 peer-reviewed articles published between 2019 and 2024 from Scopus, Web of Science, ERIC, and Google Scholar. The review identified two main themes. First, the integration of ethnomathematics and technology-based media, including digital modules, gamification, mobile apps, and augmented reality, which embed cultural practices such as weaving, batik, and traditional games into mathematics learning. Second, the impact on joyful and meaningful learning, with consistent findings of improved motivation, engagement, problem-solving, and higher-order thinking, as well as strengthened cultural identity. The findings suggest that technology-enhanced ethnomathematics not only improves cognitive outcomes but also fosters affective and cultural dimensions of learning. This approach provides a promising pathway toward culturally responsive and engaging mathematics education. Future research should explore diverse educational levels, employ longitudinal designs, and examine emerging technologies such as AI and metaverse applications in ethnomathematics-based learning.